SP6.1.7 Meta-analysis of procedural outcomes of laparoscopic-assisted endoscopic retrograde cholangiopancreatography in patients with previous Roux-en-Y gastric bypass surgery. (28th October 2021) - Hajibandeh, Shahab; Hajibandeh, Shahin; Mansour, Moustafa; Satyadas, Thomas
Abstract: Aims: To investigate the procedural outcomes of laparoscopic-assisted endoscopic retrograde cholangiopancreatography (ERCP) in patients with previous Roux-en-Y gastric bypass (RYGB) surgery. Methods: We performed a systematic review in accordance with PRISMA statement standards to identify all studies reporting procedural outcomes of laparoscopic-assisted ERCP in patients with previous RYGB. The ROBINS-I tool was used to assess the risk of bias of the included studies. Fixed-effect and random-effects models were applied to calculate pooled outcome data. Results: A total of 17 case series, enrolling 256 patients, were included. The mean age of included patients was 49. The mean procedure time was 137 minutes (95% CI 102-172). In terms of procedural success rates, the overall technical success was 95.3% (95% CI 92.5-97.5, I 2 =0%), papillary access success was 95.3% (95% CI 92.5-97.5, I 2 =0%), cannulation success was 95.3% (95% CI 92.5-97.5, I 2 =0%), sphincterotomy success was 96.1% (95% CI 93.5-98.1, I 2 =0%), and stone removal success was 95.9% (95% CI 92.4-98.4, I 2 =0%). Conversion to open was required in 4.7% (95% CI 2.5-7.6, I 2 =0%). In terms of complications, pancreatitis occurred in 4.7% (95% CI 2.3-8, I 2 =17%), cholangitis in 1.7% (95% CI 0.5 to 3.6, I 2 =0%), and perforation in 3.7% (95% CI 1.8- 6.3, I 2 =0%). The length of hospital stay was 3 days (95% CI 2-4). Conclusions: Laparoscopic-assisted ERCP seems to be feasible, effective, and a safe method to access the biliary tract in patients with previous RYGB as indicated by high technical success rates and low complication rates. There is a need for comparative evidence regarding outcomes of laparoscopic ERCP in comparison with alternative treatment options.